Polyamine-Mediated Effects of Prolactin Dictate Emergence from Mink Obligate Embryonic Diapause - Jane C. Fenelon; Arnab Banerjee; P. Lefevre; F. Gratian; Bruce D. Murphy (2016)
Embryonic diapause is an evolutionary strategy to ensure that offspring are born when maternal and environmental conditions are optimal for survival. In many species of carnivores, obligate embryonic diapause occurs in every gestation. Reciprocal embryo transplant studies indicate that embryo arrest during diapause is conferred by uterine conditions and is due to a lack of specific factors necessary for continued development. In previous studies, global gene expression analysis revealed reduced uterine expression during diapause of a cluster of genes in the mink that regulate the abundance of polyamines, including ornithine decarboxylase 1 (ODC1). In addition, in vivo inhibition of the conversion of ornithine to the polyamine, putrescine, induced a reversible arrest in mink embryonic development and an arrest in trophoblast cell proliferation in vitro. Previous studies have implicated prolactin as the principal endocrine signal to terminate diapause. In this study, uterine expression of both the progesterone and estrogen receptors remained low at reactivation whilst the prolactin receptor was expressed at all times. Treatment of mink uterine epithelial cells with varying doses of prolactin indicated that this hormone induces ODC1 expression in the uterus via pSTAT1 and mTOR, thereby regulating uterine polyamine levels. In addition, we performed global gene expression analysis on mink embryos to further explore dynamic changes during diapause and found 94 genes upregulated at reactivation from diapause. Three polyamine-related genes, including ODC1, were also upregulated at reactivation from diapause. To establish whether polyamines mitigate escape from embryonic diapause, we collected mink embryos in diapause and incubated them in vitro with putrescine. Increase in embryo volume, the first indication of emergence from diapause, was observed within the first 5 days of culture in all viable embryos treated with putrescine, and the duration of embryo survival was increased threefold. Concomitant increases were also observed in both the total number of cells and the proportion of dividing cells in putrescine-treated embryos whilst control embryos remained in the diapause state. In further studies, inhibition of polyamine synthesis abrogated proliferation in cells derived from the inner cell mass of the mink embryo, while putrescine induced dose-dependent increases in cell division. We conclude that supplementation of embryos in diapause with putrescine results in their escape from developmental dormancy. These results provide strong evidence that obligate diapause in vivo is caused by the paucity of polyamines necessary for activation of the embryo after prolactin-induced termination of diapause.